2021
DOI: 10.24018/ejedu.2021.2.5.171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mastery Learning Strategy on Secondary School Students Performance in Mathematics

Abstract: The paper examined the effects of Mastery Learning Strategy (MLS) on secondary school students’ performance in Mathematics. It investigated differences in the performance of Mathematics students in conventional and MLS groups. The study adopted a pretest, posttest and control group quasi-experimental research design. The population for the study comprises all secondary school students in Ekiti State. 60 students were the sample selected using the stratified sampling technique. Achievement Test in Mathematics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…The increasing academic performance at distinction and credit levels is likely to be a result of teachers' commitment in terms of lesson preparation, good time management, parental support for their children, intensive supervision by head teachers and other stakeholders, improved facilities, and adequate learning aids. However, this study's findings that academic performance was improving at distinction and credit levels disagree with a report by Oginni and Oginni (2019) who reported that the trends in academic performance in science-based subjects in the developing world have generally been on the decrease.…”
Section: Overall Trend Of Academic Performance In Privately Sponsored...contrasting
confidence: 99%
See 3 more Smart Citations
“…The increasing academic performance at distinction and credit levels is likely to be a result of teachers' commitment in terms of lesson preparation, good time management, parental support for their children, intensive supervision by head teachers and other stakeholders, improved facilities, and adequate learning aids. However, this study's findings that academic performance was improving at distinction and credit levels disagree with a report by Oginni and Oginni (2019) who reported that the trends in academic performance in science-based subjects in the developing world have generally been on the decrease.…”
Section: Overall Trend Of Academic Performance In Privately Sponsored...contrasting
confidence: 99%
“…The improvement in academic performance at distinction and credit levels could be because of teachers' commitment to work, setting of pupil's academic improvement targets to be met by teachers and learners, tight supervision by head teachers and other stakeholders, maintaining small classroom sizes and improved teaching-learning environment by private schools in Kigumba town council (Zuze & Leibbrandt, 2011). This finding disagrees with reports given by Thompson and Thompson (2018) and Oginni and Oginni (2019), who showed that the trend of learners' academic performance has been on the decrease in science-based subjects in most of the developing countries of the world.…”
Section: Overall Trend Of Academic Performance In Privately Funded Pr...mentioning
confidence: 68%
See 2 more Smart Citations
“…This means that learning strategies are an important thing that determines how learning takes place. Learning strategies are defined as methods that teachers use to form constructive students in a particular lesson, through the demonstration of different skills needed over time (Oginni et al, 2021).…”
Section: Introductionmentioning
confidence: 99%